Mobile Payment Protocol for Tag-to-Tag Near Field Communication (NFC) - Husni, Emir Mauludi (International Journal of Interactive Mobile Technologies (iJIM), 2012)
Communication between the near field communication (NFC) devices occurs in a very close distance of less than 10 cm. In the NFC-based payment system, close proximity between devices will increase the security of transactions. The disadvantage is the interaction between devices requires more physical activity of device owners because the device must be brought near to other devices some times. Besides requiring more physical activity, NFC-based interaction also takes a longer time because the device needs to be moved from one position to another. This paper proposed secure and efficient protocol that will reduce the physical activity of the device owners and reducing transaction time. The data exchange between merchant and payer will be executed without waiting for each other and one transaction will require two data transmissions are performed by the merchant and payer. Transactions are secured by the use of encryption on each data which sent by the merchant and payer. In addition, the protocol also guarantees the security of offline micro transactions and online macros transactions.